A Solvent-Free 2-Chloro-1-methylpyridinium Iodide (CMPI)-Mediated Biginelli Reaction for the Construction of 3,4-Dihydropyrimidin-2(1H)-ones/thiones - Kumar, Ashish; Pandey, Shashi; Gupta, Monika; Rajput, Chatrasal S. (Synthesis, 2025)
The Biginelli product dihydropyrimidinones (DHPMs) and their derivatives have enormous biological significance. This article describes the exploration of 2-chloro-1-methylpyridinium iodide (CMPI) reagent for the development of an environmentally safe, solvent-free protocol to construct the functionalized 3,4-dihydropyrimidin-2(1H)-ones/thiones. The protocol involves the three-component condensation reaction of β-keto ester, aldehyde, and urea or thiourea at elevated temperature. The key advantages of the protocol are its capacity to provide both environmental and economic benefits owing to its solvent-free conditions, short reaction times, simple workup, and good to excellent isolated yield of DHPMs.
Keywords: Biginelli reaction; CMPI; 3,4-dihydropyrimidin-2(1H)-ones/thiones (DHPMs); one-pot condensation; tri-component reaction